Experimental constraints on the long-lived radiogenic isotope evolution of the Moon. (1st June 2022) - Snape, Joshua F.; Nemchin, Alexander A.; Johnson, Tim; Luginbühl, Stefanie; Berndt, Jasper; Klemme, Stephan; Morrissey, Laura J.; van Westrenen, Wim
Abstract: This study presents the results of high pressure and temperature experiments to investigate the mineral–melt trace element partitioning behaviour for minerals predicted to have formed during the crystallisation of the Lunar Magma Ocean (LMO). The focus of this work has been particularly on determining partition coefficients for parent–daughter pairs of radiogenic elements, for LMO-relevant temperatures, pressures and compositions. The new experimental data are compared with previous studies for the same minerals and elements in order to establish best estimates for the partition coefficient of each element for evolving compositions of minerals as predicted in recent studies modelling LMO crystallisation. These estimates are used to calculate evolving parent–daughter ratios in the LMO residual melt and crystallising minerals for the four main long-lived radiogenic isotope systems that have been studied in lunar samples (Rb–Sr, Sm–Nd, Lu–Hf and U–Pb). The calculated 87 Rb/ 86 Sr, 147 Sm/ 144 Nd, and 176 Lu/ 177 Hf ratios are consistent with predictions for the mantle sources of lunar basalts and evolved lithologies. In contrast, it is difficult to explain the wide range of 238 U/ 204 Pb source ratios predicted from the Pb isotopic compositions of basaltic lunar samples. Potential explanations for this observation are discussed, with the conclusion that the Moon most likely experienced a significant loss of volatiles (including Pb), towards the end of LMO crystallisation, resulting in the dramatic U–Pb fractionation evidenced by recent sample analyses.